The political effects of threats to the nation: Evidence from the Cuban Missile Crisis - Tommaso Colussi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2021)
This paper investigates how voters respond to threats to the nation by estimating the political effects of the Cuban Missile Crisis. To establish causality, I exploit the geographical variation induced by the range of the missiles: only U.S. localities within 1,000 nautical miles from Cuba could be targeted. Difference-in-differences regressions show that target counties experienced an increase in voter turnout and support for the incumbent President's party by 5 and 3 percentage points, respectively. Finally, I find positive effects of the crisis on representatives' support for military spending and foreign intervention and on Americans' probability to serve in Vietnam.
Keywords: D72; D74; H56; D91; 330; Voting Behavior; International Crises; Cuban Missile Crisis